The EFFECT OF COOPERATIVE PROJECT BASED ONLINE LEARNING ON STUDENTS’ SPEAKING SKILL - Dini Nurfu'adiyah (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
ABSTRACT Project-based learning is a teaching model that organizes learning based on projects. The benefits of project-based learning in students include motivation, language skills, ability to function in groups, learning content, confidence, autonomy, and decision-making abilities. The inspiration driving this assessment was to investigate the impacts of the utilization of cooperative project based online learning on students’ speaking skill. The study was conducted at MTs. Mambaus Sholihin Gresik in class VII R. To know whether Cooperative project based online learning is effective, the researcher utilized a pre-experimental method in which the information calculated by a statistical formula of t-test. Pre-test that given to the students before applying cooperative- project based online learning. The students were evaluated their speaking skills in three aspects ( grammar, vocabulary, and comprehension). Post test was held after applying cooperative-project based online learning were conducted in the class. The consequence of the exploration is the mean of the pre-test was 53.7143 , and the mean of the post-test was 84.1429.